(3CQHYhf MOjkKG JbGd YfO Gdfhes - (3eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, GdNdhJj, GdMfaj , CHh GdehGgH,J (B1162 (3g` s
(3ChdgG (B:s
(3GdYHO GdabjQ eUWai GdUOjbiGdfhe ef GdfYe YdjfG deG ajg ef GdQGMI GdJi JedC GdQGMI hJLeY CTJGJkG s
(3BNQgG (B:s
(3bVi YdjgG GdehJ hjQSd GdCNQi Edi CLd eSei WQO GdTjWGf hXd jcdGDghGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B449s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs